All-Optical Reversible Logic Gates with Optically Controlled Bacteriorhodopsin Protein-Coated Microresonators. (27th June 2011) - Roy, Sukhdev; Sethi, Purnima; Topolancik, Juraj; Vollmer, Frank
Abstract : We present designs of all-optical reversible gates, namely, Feynman, Toffoli, Peres, and Feynman double gates, with optically controlled microresonators. To demonstrate the applicability, a bacteriorhodopsin protein-coated silica microcavity in contact between two tapered single-mode fibers has been used as an all-optical switch. Low-power control signals (<200  μ W) at 532 nm and at 405 nm control the conformational states of the protein to switch a near infrared signal laser beam at 1310 or 1550 nm. This configuration has been used as a template to design four-port tunable resonant coupler logic gates. The proposed designs are general and can be implemented in both fiber-optic and integrated-optic formats and with any other coated photosensitive material. Advantages of directed logic, high Q -factor, tunability, compactness, low-power control signals, high fan-out, and flexibility of cascading switches in 2D/3D architectures to form circuits make the designs promising for practical applications.